Non-tariff barriers are a manageable problem - Dieter Stentzel (Intereconomics, 1972)
With the advancing general dismantiement of tariffs, it became progressively more obvious that, apart from import duties, there are a number of other obstacles for a free flow of international trade. There are numerous rules, regulations, and restrictive practices imposed and operated by government departments and semi-official bodies which exert a more or less strong influence on the volume, the directions, and the composition of foreign trade. Such measures designed to channel trade into desired directions are collectively known as non-tariff barriers (NTBs).
Keywords: 330; Foreign Trade